KOMPETENSI DAN PERFORMANCE APPRAISAL PENGARUNYA TERHADAP PROMOSI JABATAN KARYAWAN PADA DEPARTEMEN FOOD & BEVERAGE SERVICE DI HOTEL AYODYA RESORT BALI - Ni Nyoman Seri Astini; Ida Bagus Gede Udiyana; Putu Ayu Windayanti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
This study was conducted to analyze the effect of Competency (X1) and Performance Appraisal (X2) both partially and simultaneously on promotion position (Y). The method used is quantitative. Data collection was done by distributing 135 questionnaires. All questionnaires were collected and filled in completely to be analyzed by multiple linear methods. The results of data analysis show that competency and performance appraisal have a positive and significant effect partially and simultaneously on promotion position. The result of this research proved by T-count value 3,593 larger than T-table 1,98 with a value of significant 0,000<0,05 (2) performance appraisal (X2) had positive and significant influence partially on promotion position (Y) seen from T-count value 4,686 larger than T-table 1,98 with a value of significant 0,000<0,05 and (3) Competency (X1) Performance Appraisal (X2) have positive and significant influence simultaneously to promotion position (Y) seen from F-count 129,019 larger than F-table 3,06 with a value of significant 0,000. In conclusion, competency (X1) and Performance Appraisal (X2) partially and simultaneously have a positive and significant effect on promotion position (Y).